Respuesta :

Answer:

c

Step-by-step explanation:

a. Solve

-4x + 5 = 7

-4x = 2

x = -0.5

b. Solve

3x + 1 = 10

3x = 9

x = 3

c. Solve (Correct)

2x - 3 = -11

2x = -8

x = -4

d. Solve

-2x + 7 = 1

-2x = -6

x = 3

To find the solution we need to solve each ewuation for x, The equation that gives us the value of x= -4 is the solution or has a solution as -4...

#a

[tex] \bf \: - 4x + 5 = 7 \\ \bf \: - 4x = 7 - 5 \\ \bf \: - 4x = 2 \\ \bf \: x = - \frac{2}{4} \\ \bf \: x = - \frac{1}{2} \\ \sf \: incorrect [/tex]

#b

[tex] \sf \: 3x + 1 = 10 \\ \sf \: 3x = 10 - 1 \\ \sf \: 3x = 9 \\ \sf \: x = 3 \\ \bf \: incorrect[/tex]

#c

[tex] \tt \: 2x - 3 = - 11 \\ \tt \: 2x = - 11 + 3 \\ \tt \: 2x = -8 \\ \tt \: x = - 4 \\ \rm \: correct[/tex]

#d

[tex] \rm \: 7 - 2x = 1 \\ \rm \: - 2x = 1 - 7 \\ \rm \: - 2x = - 6 \\ \rm \: x = 3 \\ \tt \: incorrect[/tex]

Thus, Option C is correct!